Pinjaman Program Kemitraan pada Peningkatan Kinerja Mitra Binaan PT Sucofindo (Persero) di Jabotabek - Heri Suprayitno; Hartrisari Hardjomidjojo; Ma'mun Sarma (Institut Pertanian Bogor, 2013)
Partnership program is a program aimed to increase the ability of small businesses to be resilient and self-sufficient through the use of funds less than 1%-2% of net profit. Partnership program has targeted in small business in the company’s region area which has been doing the business activities for at least 1 year, owning prospects to be developed and not yet having sufficient collateral to obtain bank credit and and has turnover below 200 million. PT Sucofindo (Persero) is a State-owned Business which gives loans to small and medium enterprises (SMEs) through the Program of Partnership and Environment Management. The aim of this study was to analyze: (1) financial profit margin ratio, ROTA, ROE, the circulation of work capital, (2) the changes of turnover, and (3) the changes of labours before and after the partnership loan program to the SME. The study was conducted from April to July 2011 in Jabotabek. Primary data was collected from questioner, interviews and observation, secondary data was collected from literature such as journals, magazines and books. The object was SME that has received the loan from Program of Partnership and Environment Management within 1 to 3 years. The results showed that there was an increase in the measures of SME financial performance, namely: (1) Profit Margin (PM), (2) ROTA, (3) ROE, (4) WCT, (5) Sales and (6) Labours. The conclusion of this study was that PT Sucofindo (Persero) should socialize the procedure to reach the facility of the credit of work capital to the SME.